MECHANISMS OF PERIODONTITIS - INDUCED ATHEROSCLEROSIS - Hudyono, Rikko; Sunariani, Jenny (Institute of Topical Disease Universitas Airlangga, 2010)
Nowadays CVD become the most common cause of death in US and worldwide. Atherosclerosis plays an important role in CVDs pathogenesis. Atherosclerosis decreases the elasticity of the vascular. Atherosclerosis shares the same risk factor as CVD, in which obesity, hyperlipidemia, hypertension and lack of physical activity may initiate it. However, 50% of all CVD patients are lack of the usual causes of CVD. The purpose of this review is to reveal the mechanism of periodontitis-induced atherosclerosis. Inflammation and autoimmune disease might play an important role in initiate the CVD. Periodontitis is one of the oral diseases which can cause systemic inflammation and may induce the atherosclerosis. Porphyromonas gingivalis (Pg) which is the major cause of periodontitis can induce it by expressing protein gp130 in its fimbriae. Periodontics patients are prone to have bacteremia by daily routine oral hygiene activity. Chronic bacteremia may alter the endothelial physiology, which is resulted in neointima formation, EC dysfunction, and lipid accumulation. It is concluded that periodontitis may play an important role in initiation and progression of atherosclerosis.